Pengaruh Persepsi Pelaku UMKM, Sosialisasi SAK EMKM, Tingkat Pendidikan, dan Pemahaman Akuntansi terhadap Pelaku UMKM Kota Batam - Mulyati, Sri; Buulolo, Artinus; Asyik, Nur Fadjrih (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
Micro, small, and medium enterprises will increase transparency and accountability in financial reporting, so to facilitate their access to financial resources and assist in making better business decisions. The purpose of this study was to determine the perceptions of MSME actors, SAK EMKM socialization, level of education, and understanding of accounting for MSME actors in Batam City. This type of research is quantitative. The sampling technique used the Slovin formula with a total of 90 respondents. Data testing was analyzed using multiple linear regression methods. The results of the research showed that the perceptions of MSME actors had a positive and significant effect, socialization of SAK EMKM had a positive and significant effect, level of education had a positive and significant effect, accounting comprehension had a negative effect and not significant. Simultaneous testing shows that the perceptions of MSME actors, SAK EMKM socialization, education level, and understanding of accounting have a positive and significant effect on small and medium micro business actors in Batam City.